Mammograms in cosmetic breast surgery - Shiffman, M A (Indian Journal of Plastic Surgery, 2005)
Mammograms are necessary as preoperative preparation for breast surgery in certain patients. There is a definite need for mammograms preoperatively in patients over 40 who should be obtaining mammograms on an annual basis. Under the age of 40 mammograms are up to the discretion of the surgeon. Postoperative mammograms should be obtained as a baseline 6-12 months after breast surgery.
Keywords: Mammograms; Cosmetic Surgery; Breast